How coaches shape social identity: The hidden dynamics of team sports - Pellet, J.; Louvet, B.; Tamisier, A.; Pété, E.; Guyomarch, A.; Laurin, R.; Gérat, P.; Lurquin, L.; Lepers, E.; Wiecek, S.; Fournier, A.; Perreau-Niel, G.; et al. (International Sport Coaching Journal, 2026)
Social identity plays a pivotal role in sports. Although its importance has been highlighted, little is known about how coaches shape its development through the coach-athlete relationship and motivational climate. This study explores the influence of players` perceived coach-athlete relationship and motivational climate on social identity in team sports. A total of 210 team sport young elite male athletes ( M age = 16.31, SD age = 1.00) completed an online survey measuring their social identification with the team, perception of the coach-created motivational climate, and quality of relationship with their coach. Linear mixed-effects models revealed that commitment was positively related with ingroup ties ( R 2 p = .03), cognitive centrality ( R 2 p = .05), and ingroup affect ( R 2 p = .03). An empowering motivational climate was also related with ingroup ties ( R 2 p = .05) and ingroup affect ( R 2 p = .02), whereas a disempowering climate had no effect. Interaction effects showed that a medium or low motivational climate strengthened the positive relationship between commitment and ingroup affect ( R 2 p = .06), whereas a low motivational climate generated a negative relation between closeness and ingroup affect ( R 2 p = .02). These findings demonstrate the effect of coaches on athletes` team identification in building supportive relationships and empowering environments.